Training on Developing Lesson Plan Through Utilizing Deep Learning Technology within the TPACK for Sociology Teachers in Karanganyar Regency - Atik Catur Budiati; Siany Indria Liestyasari; Bagas Narendra Parahita (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Background: The improvement of sociology learning quality at the Senior High School level requires teachers to be able to integrate pedagogical technology and content comprehensively and contextually.Aims: This research is designed to equip teachers with the skill to develop teaching modules based on the utilizing deep learning technology within the TPACK.   Methods: Training was carried out in four stages: strengthening concept, composing modules, learning simulation, and feedback and reflection. The training method was participatory and contextual in nature, by emphasizing direct practice and collaboration between participants.Results: The result of training shows that teachers experience significant improvement in comprehending TPACK and are capable of composing lesson plans that integrate sociological content, reflective and problem-based approach. Evaluation outcomes revealed a significant improvement in participants’ comprehension, with average scores increasing from 70 (pretest) to 90 (posttest). The product yielded reflects in-depth contextual learning and involves technology use meaningfully. This training contributes to the transformation of teachers’ role as the facilitator of learning in digital era. Conclusion: The implication involves improved professionalism, digital literacy, and strengthened contextual learning strategy. The training resulted in an average increase of 20 points, signifying a shift in teachers' views on the holistic utilizing of technology, pedagogy, and content. The recommendation based on this activity is the need for sustainable facilitation and training model replication for other social science subjects.